Template Secondary Structure Promotes Polymerase Jumping During PCR Amplification - V.K. Viswanathan; Kevin Krcmarik; Nicholas P. Cianciotto (BioTechniques, 1999)
Pairs of primers flanking known miniTn10 transposon insertion sites were used to confirm the presence of the transposon in DNA isolated from Legionella pneumophila mutants. It was expected that the polymerase chain reaction products derived from the mutant template would be larger than those from the wild-type (WT) template due to the presence of the 1.8-kb transposon. Instead, it was observed that the mutant template yielded a product of almost the same size as that yielded by WT template. We present evidence to indicate that the aberrant product from the mutant template is a direct result of secondary structure of the template resulting from an inverted repeat sequence present in the miniTn10 transposon.